2017
DOI: 10.1021/acs.jpcc.7b03107
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulation of Singlet Fission in Single Crystalline Pentacene by Functional Mode Vibronic Theory

Abstract: We have applied our functional mode framework for singlet fission to pentacene, a prototypical organic material for multiple exciton generation. It was found that singlet fission in pentacene occurs predominantly through a coherent process mediated by a virtual charge-transfer (CT) intermediate, which lies slightly above the photoexcited S1S0 state. This energetic near-degeneracy facilitates a substantial vibronic superposition, leading to a rapid transition rate of 25.1 ps–1. By contrast, the direct S1S0 → T1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…A detailed description of the computational calculations can be found in Supplemental Information. As shown in Figure 2B, we denote the ground state, singlet excited state, charge-transfer state, correlated triplet pair, and decoupled triplet dimer as 1 (S 0 S 0 ), 1 (S 1 S 0 ), CT, 1 (T 1 T 1 ), and T 1 + T 1 , respectively, and their constituent spin configurations were illustrated in our previous studies (Elenewski et al., 2017a, Elenewski et al., 2017b). Geometry optimization was carried out on all spin states before their relative energies are determined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the computational calculations can be found in Supplemental Information. As shown in Figure 2B, we denote the ground state, singlet excited state, charge-transfer state, correlated triplet pair, and decoupled triplet dimer as 1 (S 0 S 0 ), 1 (S 1 S 0 ), CT, 1 (T 1 T 1 ), and T 1 + T 1 , respectively, and their constituent spin configurations were illustrated in our previous studies (Elenewski et al., 2017a, Elenewski et al., 2017b). Geometry optimization was carried out on all spin states before their relative energies are determined.…”
Section: Resultsmentioning
confidence: 99%
“…As previously discussed, the formation of 1 (T 1 T 1 ) could proceed through the direct, the CT-mediated, and the sequential mechanisms. To reconcile which mechanism is responsible for the fast and isotropic formation of 1 (T 1 T 1 ) in hexacene, we employed our functional mode vibronic theory that has been successfully applied to investigate singlet fission in tetracene and pentacene (Elenewski et al., 2017a, Elenewski et al., 2017b). If the direct mechanism is followed, 1 (T 1 T 1 ) is formed without the aid of any CT intermediate.…”
Section: Discussionmentioning
confidence: 99%
“…20 In our previous theoretical study, SF was found to be facilitated by a few aromatic-ring-stretching modes centered at 1580 cm −1 in single-crystalline pentacene. 46 According to the nonadiabatic transition theory, 47 in the absence of light irradiation, energy conservation between reactant and product electronic states can be fulfilled only through thermal fluctuations, which also drive the system toward the diabolic point where the nonadiabatic coupling is nonvanishing. In organic molecular crystals such as tetracene, pentacene, and hexacene, their normal modes can be readily characterized, thanks to crystalline symmetry and weak interactions between lattice-site occupants.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, intra‐ and intermolecular vibrational modes have been discussed to impact SF in various ways [4,5,7,9–20] . For TET and PEN, several modes have been identified as key contributions, such as the modes at 1440 cm −1 and 1540 cm −1 in TET [9] or the mode at 1150 cm −1 , which is discussed to promote mixing between the singlet and the triplet pair state in PEN [18,25] . Furthermore, while SF in PEN has experimentally been found to be robust against variations in structural properties and intermolecular interaction strength, [52] SF of TET shows a sensitivity to the molecular arrangement [53] .…”
Section: Resultsmentioning
confidence: 99%
“…This concerns intra‐ as well as intermolecular vibrations. For example, intramolecular vibrational modes between 300 and 1550 cm −1 have been found to be important for efficient SF in acenes [9,17,20,22–25] with a high sensitivity of SF rates to the frequency of the considered modes [17,22,25] and were found to induce vibronic coherences on timescales longer than the singlet fission process itself [19–21,26–28] . Intermolecular vibrations have been discussed as an additional contribution to charge transfer mediated SF via non‐adiabatic population transfer [11,20,28] and have been demonstrated to significantly affect SF rates and the subsequent triplet‐pair separation process [27,29–36] …”
Section: Introductionmentioning
confidence: 99%